2007
DOI: 10.1007/s00422-007-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model of thoracic differentiation for the control of turning in the stick insect

Abstract: Leg movements of stick insects (Carausius morosus) making turns towards visual targets are examined in detail, and a dynamic model of this behaviour is proposed. Initial results suggest that front legs shape most of the body trajectory, while the middle and hind legs just follow external forces (Rosano H, Webb B, in The control of turning in real and simulated stick insects, vol. 4095, pp 145-156, 2006). However, some limitations of this explanation and dissimilarities in the turning behaviour of the insect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…We have found that the stepping patterns of the intact straight walking stick insect on the slippery surface are qualitatively very similar to those observed for freely walking stick insects (Cruse, 1976;Rosano and Webb, 2007) or tethered stick insects walking on a sphere (Dürr, 2005;Dürr and Ebeling, 2005). Similar movement patterns have also been reported for stick insects walking on an oiled glass surface and on a mercury surface (Graham and Cruse, 1981;Cruse and Epstein, 1982;Epstein and Graham, 1983).…”
Section: Straight Walking and Turning In The Intact Animalsupporting
confidence: 78%
See 2 more Smart Citations
“…We have found that the stepping patterns of the intact straight walking stick insect on the slippery surface are qualitatively very similar to those observed for freely walking stick insects (Cruse, 1976;Rosano and Webb, 2007) or tethered stick insects walking on a sphere (Dürr, 2005;Dürr and Ebeling, 2005). Similar movement patterns have also been reported for stick insects walking on an oiled glass surface and on a mercury surface (Graham and Cruse, 1981;Cruse and Epstein, 1982;Epstein and Graham, 1983).…”
Section: Straight Walking and Turning In The Intact Animalsupporting
confidence: 78%
“…As of now, there are no electrophysiological results in the stick insect elucidating the mechanism underlying turning. However, behavioral analysis has suggested that the front legs take a leading role in the organized execution of turns (Dürr and Ebeling, 2005) and a body trajectory analysis by Rosano and Webb (Rosano and Webb, 2007) supports this finding but suggested the additional contribution to turning by the posterior legs.…”
Section: Straight Walking and Turning In The Intact Animalmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominance of the front leg movements in generating directional changes and adjustments has been reported in stick insects turning in response to visual stimuli (Dürr and Ebeling, 2005;Rosano and Webb, 2007) with the role of the middle legs still discussed (Rosano and Webb, 2007). There is no evidence in this species for hind legs making an active contribution to steering.…”
Section: Contribution Of Legs To Turning In Other Insectsmentioning
confidence: 94%
“…Different forms of asymmetric walking have been observed: stick insects increase their stepping frequency or step length on one side of the thorax relative to the other (Graham, 1972). Video recordings of walking stick insects performing visually induced turning (Dürr and Ebeling, 2005;Rosano and Webb, 2007) and of cockroaches with tactile-induced turning (Mu and Ritzmann, 2005) have all demonstrated the dominant role of the front legs in shaping walking direction.…”
Section: Introductionmentioning
confidence: 99%